Knockdown of CDKN1C (p57(kip2)) and PHLDA2 results in developmental changes in bovine pre-implantation embryos. - Ashley M Driver (Public Library of Science (PLoS), 2013)
Imprinted genes have been implicated in early embryonic, placental, and neonatal development and alterations in expression levels of these genes can lead to growth abnormalities and embryonic lethality. However, little is known about the functions of bovine imprinted genes during the pre-implantation period. Therefore, the objective of this study was to assess the influence of altered expression of imprinted genes on developmental progress of embryos using small interfering RNA (siRNA). Expression levels of 18 imprinted genes (MAGEL2, UBE3A, IGF2R, NAP1L5, TSSC4, PEG3, NDN, CDKN1C, PHLDA2, MKRN3, USP29, NNAT, PEG10, RTL1, IGF2, H19, MIM1, and XIST) were compared between embryos reaching the blastocyst stage and growth-arrested embryos (degenerates) using quantitative real-time PCR (qRT-PCR). Ten genes were found to be differentially expressed between blastocysts and degenerates. The CDKN1C gene showed the highest upregulation in blastocysts whereas PHLDA2 was highly expressed in degenerates. To assess whether the observed differential gene expression was causative or resultant of embryo degeneration, these genes were selected for functional analysis using siRNA. Injection of siRNA specific to PHLDA2 into one-cell zygotes resulted in a substantial increase in blastocyst development, whereas injection of CDKN1C-specific siRNA resulted in a 45% reduction (P = 0.0006) in blastocyst development. RNA-Seq analysis of CDKN1C-siRNA-injected vs. non-injected embryos revealed 51 differentially expressed genes with functions in apoptosis, lipid metabolism, differentiation, and cell cycle regulation. Gene ontology analysis revealed nine pathways related to cell signaling, metabolism, and nucleic acid processing. Overall, our results show that proper expression levels of the imprinted genes CDKN1C and PHLDA2 are critical for embryo development, which suggests that these genes can be used as markers for normal blastocyst formation.